The HCN Channel Blocker ZD7288 Induces Emesis in the Least Shrew (Cryptotis parva) - Zhong, W.; Darmani, N. A. (Frontiers in Pharmacology, 2021)
Subtypes (1-4) of the hyperpolarization-activated cyclic nucleotide-gated (HCN) channels are widely expressed in the central and peripheral nervous systems, as well as the smooth muscle cells of many organs. They mainly serve to regulate cellular excitability in these tissues. The HCN channel blocker ZD7288 has been shown to reduce apomorphine-induced conditioned taste aversion on saccharin preference in rats suggesting potential antinausea/antiemesis effects. Currently, in the least shew model of emesis we find that ZD7288 induces vomiting in a dose-dependent manner, with maximal efficacies of 100% at 1 mg/kg (i.p.) and 83.3% at 10 µg (i.c.v.). HCN channel subtype (1-4) expression was assessed using immunohistochemistry in the least shrew brainstem dorsal vagal complex (DVC) containing the emetic nuclei (area postrema (AP), nucleus tractus solitarius and dorsal motor nucleus of the vagus). Highly enriched HCN1 and HCN4 subtypes are present in the AP. A 1 mg/kg (i.p.) dose of ZD7288 strongly evoked c-Fos expression and ERK1/2 phosphorylation in the shrew brainstem DVC, but not in the in the enteric nervous system in the jejunum, suggesting a central contribution to the evoked vomiting. The ZD7288-evoked c-Fos expression exclusively occurred in tryptophan hydroxylase 2-positive serotonin neurons of the dorsal vagal complex, indicating activation of serotonin neurons may contribute to ZD7288-induced vomiting. To reveal its mechanism(s) of emetic action, we evaluated the efficacy of diverse antiemetics against ZD7288-evoked vomiting including the antagonists/inhibitors of: ERK1/2 (U0126), L-type Ca2+ channel (nifedipine); store-operated Ca2+ entry (MRS 1845); T-type Ca2+ channel (Z944), IP3R (2-APB), RyR receptor (dantrolene); the serotoninergic type 3 receptor (palonosetron); neurokinin 1 receptor (netupitant), dopamine type 2 receptor (sulpride), and the transient receptor potential vanilloid 1 receptor agonist, resiniferatoxin. All tested antiemetics except sulpride attenuated ZD7288-evoked vomiting to varying degrees. In sum, ZD7288 has emetic potential mainly via central mechanisms, a process which involves Ca2+ signaling and several emetic receptors. HCN channel blockers have been reported to have emetic potential in the clinic since they are currently used/investigated as therapeutic candidates for cancer therapy related- or unrelated-heart failure, pain, and cognitive impairment.